Gram stain evaluation in dermatovenereology clinic and microbiology laboratories: case series - Kusumadewi, Yolanda Pitra; Kholidah, Siti Nurhayati; Susetiati, Devi Artami; Nuryastuti, Titik (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Introduction: The normal vaginal flora consists of aerobic and anaerobic bacteria; Lactobacillus sp. is the main microorganism in the vagina. In bacterial vaginosis, there is a decrease in Lactobacillus sp. and an increase in pathogenic bacteria. Direct gram staining of vaginal fluid is the standard microbiological method for diagnosing bacterial vaginosis. Gram staining allows us to distinguish between gram-positive and gram-negative bacteria based on differential staining with crystal violet iodine complex and safranin. This study aimed to evaluate and compare the gram stain results between the dermatovenereology clinic and microbiology laboratories. Case description: Direct gram staining of vaginal or cervical swabs was carried out on women aged 19 years, women aged 29 years, and women aged 40 years. The gram staining was carried out at the dermatovenereology clinic and microbiology laboratory with different results between the two locations. Conclusion: It is important to evaluate the process of taking vaginal fluid samples, making smears/slides, and gram staining so that the quality of the examination results is maintained